Practical Aspects of Declarative Languages 17th International Symposium, PADL 2015, Portland, OR, USA, June 18-19, 2015. Proceedings - Pontelli, Enrico; Son, Tran Cao.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 17th International Symposium on Practical Aspects of Declarative Languages, PADL 2015, held in Portland, OR, USA, in June 2015. The 10 revised papers presented were carefully reviewed and selected from numerous submissions. The papers cover all forms of declarative concepts, including, functional, logic, constraints, etc.
Ontology-Driven Data Semantics Discovery for Cyber-Security -- State Space Planning Using Transaction Logic -- On Compiling Linear Logic Programs with Comprehensions, Aggregates and Rule -- Declaratively Solving Google Code Jam Problems with Picat -- Reactive Single-Page Applications with Dynamic Dataflow -- CHR(Curry): Interpretation and Compilation of Constraint Handling Rules in Curry -- Implementation and Performance of Probabilistic Inference -- A Haskell Implementation of a Rule-Based Program Transformation for C Programs -- On Logic Programming Representations of Lambda Terms: de Bruijn Indices, Compression, Type Inference, Combinatorial Generation, Normalization -- Programming Microcontrollers in OCaml: the OCaPICProject.
Keywords: Programming languages (Electronic computers).; Computer programming; Computer logic; Software engineering; Programming Languages, Compilers, Interpreters; Programming Techniques; Logics and Meanings of Programs; Software Engineering